(untitled) (Journal of Asian Development Studies, 2026)
The Study examines the influential role of governance in the nexus between financial technology and sustainable development. Using statistical techniques such as ordinary least squares, fixed-effects models, and generalized method of moments (GMM) models, the study finds a complex relationship. The findings indicate that, in the absence of governance as a moderating factor, fintech is negatively and significantly associated with the Sustainable Development Goals, reflecting challenges such as weak regulatory frameworks, limited financialliteracy, high implementation costs, and inadequate technological infrastructure. However, when governance quality is introduced as a moderating factor, fintech has a strong, significant positive influence on the SDGs. These results suggest that effectivegovernance mitigates fintech-related risks while enhancing its potential to drive inclusive growth, reduce poverty, foster green innovation, and improve energy efficiency. Furthermore, the analysis highlights the critical role of governance in shaping financial and technological systems by strengthening institutional quality, improving regulatory mechanisms, and promoting sustainable economic policies. Policymakers are encouraged to implement robust regulations, incentivize fintech-driven green initiatives, and integrate environmental considerations into financial innovation. By aligning fintech development with sound governance frameworks, countries can accelerate progress toward achieving the SDGs, ensuring that technological and financial advancements contribute to long-term sustainability.